Large for Gestational Age and Obesity-Related Comorbidities - Hong, Yong Hee (J Obes Metab Syndr, 2021)
Both small for gestational age and large for gestational age (LGA) size at birth are associated with metabolic complications throughout life. The long-term consequences of LGA have been investigated in only a few studies. LGA is thought to be associated with early obesity and metabolic risk. Understanding how LGA can influence later obesity risk is important for pediatric obesity interventions. Pregnant women who are overweight or obese are at high risk of having LGA babies. Infants born LGA are at increased risk of becoming overweight or obese children, adolescents, and young adults and can have an increased risk of metabolic syndrome later in life and giving birth to LGA offspring. Education and intervention for weight control before and during pregnancy should be conducted to prevent LGA births. Particular attention is needed for women of childbearing age who are diabetic and obese, which could be the starting point for lifelong management of obesity.